Newborn Hemoglobinopathy Screening Podcasts (Out of Print) - James Harper (Association of American Medical Colleges, 2006)
Abstract This series of podcasts cover the confirmatory testing, anticipatory guidance, and genetic counseling issues confronted by the primary care provider with a newborn found to have an abnormal hemoglobinopathy screen. The podcasts are titled by the abnormality listed in the report (e.g., FAS, rather than sickle cell trait.) Each podcast is 5-8 minutes long and all are .mp3 format. These podcasts are being used by the Nebraska Newborn Screening program and is a model for other podcasts regarding common inborn errors of metabolism.